Navigating a communication paradox : how an Italian tourism organisation managed communication via Facebook during Covid-19 - Igonina, Anna (2021)
Destination marketing helps places nowadays to attract tourists and to form a positive image of the destination. However, destination marketing becomes a challenging task during the ongoing crisis. Due to the outbreak of the Covid-19 disease and implemented travel restrictions, tourism organisations faced a communication paradox: they could not perform their main task – to attract tourists. Nevertheless, they have to maintain communication on social media with the target audience, promote destinations, and navigate the paradox in communication. The call for papers from destination marketing scholars about the effect of the Covid-19 on tourism and the need for additional research on the usage of social media in crisis communication led to the development of the key objective of this thesis, which is to understand how, during the Covid-19 pandemic, the destination marketing organisation (DMO) in Italy used Facebook to navigate the paradox between (a) inviting foreigners to visit Italy and (b) telling them not to visit Italy yet because of the pandemic. In the study effect of the Covid-19 pandemic on the DMO communication is analysed with the paradox lens. Recent research suggests utilising paradox theory to study the effects of Covid-19. For the research has been selected Italy, as it was the first country to implement travel restrictions and the importance of tourism for its economy. The aim of the re- search was achieved via studying prior literature related to the topic and conducting both qualitative and quantitative analysis of Facebook posts of Italia.it community, during the first wave of the pandemic, from the 10th of March 2020 till the 3rd of June 2020. As a result of the study was found that to navigate the paradox between invitational and cautionary messages, the DMO of Italy used a key message in posts: ‘Italy comes to you’(i.e., the DMO invited followers to explore Italy via virtual tours). Thus, the pandemic restrictions have been communicated, however open invitations and cautions were avoided by the DMO. Besides, the study explored how users responded in terms of engagement to the messages communicated during the first wave of the Covid- 19 pandemic.